Intrinsic Motivation that Influences the Loyalty of Hotel Employees - Toh Pei Sung; Awangku Hassanal Bahar Bin Pengiran Bagula; Janie Liew-tsonis; Charlie Albert Lasuin; Juliana Langgat (2013)
The tourism industry has gained prominence long ago in Malaysia and it is largely responsible in contributing to the Malaysian’s Gross Domestic Product or GDP while creating employment opportunities to the various service sectors that are assisting in the developing and modernizing the economy. The hotel sector is one of the tourism sub-sectors that have been identified as the key growth area for the service industry in Malaysia. Challenges for the hotel sector in Malaysia such as high labor turnover and the difficulty in retaining the hotel employees are the main research issues that formed the setting of this paper. This research is addressing this issue through filling in the gap of the research area by understanding and examining the motivational factors that would actually motivate the hotel employees to maintain their engagement with their employer. The specific objective of this paper is to identify if there is a significant relationship between intrinsic motivation and loyalty or not. This quantitative research was carried out among operational employees in star-rated hotels. In Kota Kinabalu, Malaysia, as it is evidential that the hotel sector experiencing high turnover that increase the cost of the human resource management. Results of the paper suggested that responsibility and work itself are the two most important factors in motivating hotel employees and that employees are more likely to be committed and engaged with their employer when the